SOSIALISASI BUDIDAYA TANAMAN OBAT KELUARGA (TOGA) DI PEKARANGAN RUMAH MASYARAKAT GAMPONG JURONG PEUJEURA, ACEH BESAR - Wahyuni, Fitri; Savitri; Eka Puspita, Diah; Al Fadhil, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The average houses of the Jurong Peujeura Village community have limited yards and are only planted with ornamental plants, so it is very necessary to conduct socialization about the benefits of planting TOGA in the yard. This community service activity aims to (a) provide knowledge about the benefits of TOGA and increase family income (b) understand the importance of preserving TOGA plants as a tradition and heritage in the future (c) optimize the use of home yard land by cultivating TOGA plants. Socialization and counseling are carried out by providing oral material and discussions with community service participants, then evaluation is carried out by giving a quiz at the end of the activity. This Community Service activity is very useful, especially for mothers in Jurong Peujeura Village, there are 12 types of TOGA whose functions and benefits are explained. Results showed of the pre-test/quiz show that the Jurong Peujeura community has understood the various types and methods of cultivating TOGA in the yard. Based on the results of the discussion, planting medicinal plants in the yard in Jurong Peujeura Village has not been optimized, due to the lack of community understanding about the importance of TOGA plants to meet the needs of family herbal medicines.